Micronutrients and exercise: anti-oxidants and minerals - Clarkson, P. M. (Journal of Sports Sciences, 1995)
Exercise has been shown to increase indirect measures of lipid peroxidation. However, exercise and training appear to augment the body's anti-oxidant defence system. Whether this augmented defence system can keep up with the increase in lipid peroxidation with exercise is not known. Iron depletion is experienced by many athletes, especially female endurance athletes and adolescents, but iron deficiency anaemia is rare. Iron depletion could affect the ability to train and recover from strenuous exercise, but this has not been examined. There is a concern that female athletes, especially adolescents, are not ingesting sufficient calcium, and this may affect the development of peak bone mass and increase the risk of bone fractures. Further research is needed on mineral and trace mineral intake and loss in athletes. It appears that most athletes have adequate status of chromium, zinc, phosphate and magnesium. Athletes who are restricting energy intake to achieve a low body mass (for example, endurance runners), may not have adequate vitamin or mineral status. More data are needed on vitamin/mineral status of athletes from underdeveloped countries. The general recommendation for athletes is that foods rich in anti-oxidants and minerals should be ingested rather than supplements.